Metal Y-doped YAG transparent ceramic and preparation method and application thereof

By using a method to prepare YAG transparent ceramics doped with metallic Y, the problems of insufficient thermal conductivity and mechanical strength of YAG transparent ceramics have been solved, resulting in YAG transparent ceramics with high transparency and high thermal conductivity, which are suitable for medium and high energy physics and medical devices.

CN118344135BActive Publication Date: 2025-11-04MINDU INNOVATION LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310056484.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-11-04
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

The thermal conductivity and mechanical strength of existing YAG transparent ceramics cannot meet the requirements of practical applications, and traditional sintering methods introduce impurity elements and result in excessively large grains.

Method used

By employing a metal Y doping method, low-melting-point metal Y is added through the chemical formula (YxY1-x)3Al5O12-3x. Combined with solid-state synthesis, ethanol is used as a solvent for sand milling, and vacuum sintering is performed. This avoids the addition of sintering aids and lowers the sintering temperature, thus preparing YAG transparent ceramics with high transparency and high thermal conductivity.

Benefits of technology

It achieves high transmittance, excellent mechanical properties and high thermal conductivity, and has a simple manufacturing process and low cost, making it suitable for medium and high energy physics and medical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118344135B_ABST
    Figure CN118344135B_ABST
Patent Text Reader

Abstract

The application discloses metal yttrium doped YAG transparent ceramic and a preparation method and application thereof. The metal yttrium doped YAG transparent ceramic has higher thermal conductivity and more excellent mechanical strength, and can be used as a window material solution in material science, biology and physics. In addition, the low-melting-point metal Y powder doped in the YAG system transparent ceramic has the effect of a sintering aid, can make the crystal lattice be distorted to form a solid solution and a vacancy type solid solution, can reduce the sintering temperature, is helpful to sintering, can reduce the influence of other impurity elements, and can obtain the ceramic with more excellent performance. The application dopes the metal Y powder and YAG raw materials on the basis of traditional solid-phase synthesis ceramic, does not add other element sintering aids and does not add a binder, only mixes the metal Y powder and the raw materials uniformly by introducing the metal Y powder, and sintering is carried out under high vacuum and high temperature conditions, so that the metal Y doped YAG transparent ceramic with high transmittance is obtained for the first time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of YAG ceramic and its synthesis, and particularly relates to a metal Y doped YAG transparent ceramic and a preparation method and application thereof. BACKGROUND

[0002] The YAG transparent ceramic belongs to a cubic system (wherein YAG is an abbreviation of yttrium aluminum garnet) and has a garnet structure. The YAG transparent ceramic has good stability, especially good thermal stability and high temperature mechanical properties, and thus can be widely used in fields of laser substrate materials, optical lenses, high energy physics, medical devices and the like. A pure YAG transparent ceramic has a relatively high sintering temperature, and an appropriate amount of additives (such as CaO, MgO, SiO2, LiF and the like) can effectively promote sintering of the ceramic. However, new impurity elements are also brought in, and the ceramic grains sintered by some additives are also often large, resulting in that the thermal conductivity and mechanical strength of the prepared YAG transparent ceramic cannot meet the requirements of actual application. It is urgent to develop a new YAG transparent ceramic with higher thermal conductivity and excellent mechanical strength. SUMMARY

[0003] To improve the above problems, the application provides the following technical scheme.

[0004] A metal Y doped YAG transparent ceramic has a chemical formula of (Y x Y 1-x )3Al5O 12-3x ; wherein 0 < x ≤ 0.01; the first Y represents metal Y and exists in a doped form; and the second Y comes from yttrium in yttrium oxide and exists in a crystal lattice as a main matrix.

[0005] In some embodiments, the Y element in the ceramic comes from yttrium oxide Y2O3 and metal Y, wherein Y2O3 is the main matrix.

[0006] Research shows that metal Y has a relatively low melting point and does not react with ethanol. Adding low-melting-point metal Y can cause distortion of the crystal lattice to form a solid solution and a vacancy type solid solution, can reduce the sintering temperature, is helpful for sintering, and can also reduce the influence of other impurity elements. The metal Y doped YAG transparent ceramic of the application has higher thermal conductivity and excellent mechanical strength than the traditional YAG transparent ceramic, and has high application value for preparation of YAG transparent ceramic devices.

[0007] In some embodiments, x = 0.0001-0.01. For example, x can be 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009 or 0.01. Preferably, x = 0.0005-0.01; more preferably, x = 0.001-0.005.

[0008] In some embodiments, the transmittance of the metal Y doped YAG transparent ceramic is greater than 70%; for example, greater than 72%; in particular, not less than 79%; more particularly, not less than 80% or not less than 82%; even more particularly, up to 85%.

[0009] In some embodiments, the grain size of the metal Y doped YAG transparent ceramic is smaller than that of the YAG transparent ceramic doped with Si type additive; in particular, the grain size is 3-6 μm.

[0010] In some embodiments, the grains of the metal Y doped YAG transparent ceramic are dense, the grain boundaries are clear, and no obvious pores exist.

[0011] In some embodiments, the average thermal conductivity of the metal Y doped YAG transparent ceramic is greater than or equal to 10 w / (m·K); for example, greater than or equal to 12 w / (m·K); more for example, greater than or equal to 14 w / (m·K); even more for example, greater than or equal to 15 w / (m·K); further, greater than or equal to 16 w / (m·K); up to 17 w / (m·K).

[0012] In some embodiments, the Vickers hardness of the metal Y doped YAG transparent ceramic is greater than 14 GPa; for example, not less than 15 GPa; more for example, not less than 16 GPa; even more for example, not less than 18 GPa; further, up to 19 GPa.

[0013] The present application also provides a preparation method of the metal Y doped YAG transparent ceramic, which comprises the following steps:

[0014] 1) mixing a certain amount of (i) Y2O3, (ii) Al2O3 and (iii) metal Y according to the composition of the chemical formula (Y x Y 1-x )3Al5O 12-3x , to obtain a raw material mixture, and further adding ethanol to mix to obtain a mixture;

[0015] 2) sand milling the mixture in step 1) and drying;

[0016] 3) preliminary pressing, glue removal, cold isostatic pressing;

[0017] 4) vacuum sintering, to obtain the metal Y doped YAG transparent ceramic.

[0018] The solid phase synthesis method known to those skilled in the art is a commonly used method for preparing YAG transparent ceramic, and is a relatively simple method capable of obtaining a relatively uniform and well-dispersed powder. However, as mentioned in the background, there are some defects, such as the need to add an additive that will introduce impurity elements, the lattice size of the prepared YAG transparent ceramic is large, and the crystal grains are not dense enough. In the above preparation method of the metal Y doped YAG transparent ceramic of the present application, no sintering additive is added, and by introducing metal Y with a low melting point, the sintering temperature of the ceramic is reduced, and a high-transparency YAG transparent ceramic is obtained. The preparation process of the method is simple, the cycle is short, the cost is low, and a transparent YAG transparent ceramic can be obtained at a relatively low temperature.

[0019] Further research has found that the metal Y powder used in the preparation process of the metal Y doped YAG transparent ceramic has low solubility in normal temperature water and alcohol, is chemically stable, but is sensitive to air and easy to get damp, and is a flammable substance that needs to be sealed for storage. In addition, metal powder particles are often large and are not easy to refine in the conventional preparation process, so it is often necessary to further process the metal Y to refine it to a size similar to that of the YAG powder to achieve effective mixing.

[0020] In some embodiments, in step 1), the ethanol is anhydrous ethanol; and the mass of the ethanol is 80-120% of the mass of the raw material mixture, for example 80%, 90%, 100%, 110%, or 120%.

[0021] In some embodiments, in step 2), the drying temperature is 40-90°C, for example 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90°C, and can exemplarily be 45-75°C.

[0022] In some embodiments, in step 2), the drying time is 10h-48h, for example 10h, 12h, 24h, 30h, 40h, or 48h.

[0023] In some embodiments, in step 2), the mixture after drying is further ground, then sieved, and then step 3) is performed.

[0024] In some embodiments, in step 2), a 50-150μm sieve is used in the sieving step.

[0025] In some embodiments, in step 3), the initial pressing is performed in a steel die.

[0026] In some embodiments, in step 3), the initial pressing is performed at a pressure of 5-20 MPa, for example 5 MPa, 8 MPa, 10 MPa, 15 MPa or 20 MPa.

[0027] In some embodiments, in step 3), the initial pressing is performed for a time of 10-60 s, for example 10 s, 20 s, 30 s, 40 s, 50 s or 60 s.

[0028] In some embodiments, in step 3), the degumming is performed in an oxygen atmosphere. The oxygen atmosphere can be a pure oxygen atmosphere or an oxygen-containing atmosphere, for example an air atmosphere.

[0029] In some embodiments, in step 3), the degumming is performed at a temperature of 100-1000 °C, in particular 200-900 °C, and more particularly 400-800 °C, for example 400 °C, 450 °C, 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C or 800 °C.

[0030] In some embodiments, in step 3), the temperature increase in the degumming process is performed in two stages, in the first stage, the temperature is increased from room temperature to 100-400 °C at a rate of ≤ 200 °C / h (for example 100 °C / h, 180 °C / h); in the second stage, the temperature is increased from 200-400 °C to 700-900 °C at a rate of ≤ 150 °C / h (for example 80 °C / h, 120 °C / h).

[0031] In some embodiments, in step 3), the degumming is performed for a time of 5-20 h, for example 5-15 h, for example 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.

[0032] In some embodiments, in step 3), the cold isostatic pressing is performed at a pressure of 100-300 MPa, preferably 150-250 MPa.

[0033] In some embodiments, in step 3), the cold isostatic pressing is performed for a time of 100-150 s, for example 100 s, 110 s, 120 s, 130 s, 140 s or 150 s.

[0034] In some embodiments, in step 4), the sintering temperature is 1650-1950 °C, preferably 1700-1850 °C.

[0035] In some embodiments, the vacuum in the vacuum sintering is at least 10-2 Pa, for example, is 10 -2 Pa~10 - 5 Pa, specifically, can be 10 -2 Pa~10 -3 Pa. Wherein, sintering under vacuum condition is beneficial to eliminate air holes.

[0036] In some embodiments, step 4) specifically comprises, vacuum sintering and holding for a certain time, then annealing, polishing, to obtain the metal Y doped YAG transparent ceramic.

[0037] In some embodiments, in step 4), the holding time is 5h~30h, specifically, can be 5h, 10h, 15h, 20h, 25h or 30h.

[0038] The application also provides the application of the metal Y doped YAG transparent ceramic, which can be widely used in the fields of high-energy physics, medical equipment, etc.

[0039] The application also provides the following technical solutions:

[0040] A transparent armor material or laser gain medium material, comprising the metal Y doped YAG transparent ceramic described above.

[0041] Compared with the prior art, the application has the following beneficial effects:

[0042] The application provides a brand new metal Y doped YAG transparent ceramic, which has many characteristics such as high transmittance, high thermal conductivity and excellent mechanical properties.

[0043] The application also provides a preparation method of the metal Y doped YAG transparent ceramic, and the application adopts a solid phase synthesis method to prepare the metal Y doped YAG transparent ceramic. In the preparation process, solvent ethanol is added to the mixed oxides of raw materials and sand grinding is performed, and after sand grinding, the mixed oxides are uniformly mixed with the powder, so that high activity can be achieved, and finally the green body is sintered in vacuum, so that the metal Y doped YAG transparent ceramic of the application can be obtained at a lower temperature.

[0044] Further, the metal Y doped YAG transparent ceramic prepared by the application can be widely used in the fields of high-energy physics, medical equipment, etc., and is an ideal transparent armor material and laser gain medium material. DETAILED DESCRIPTION

[0045] Figure 1 It is a real object picture of the metal Y doped YAG transparent ceramic of the application embodiment 1, the application embodiment 2 and the application embodiment 3.

[0046] Figure 2X-ray diffraction patterns of Example 1, Example 2, Example 3, respectively.

[0047] Figure 3 is a scanning electron microscope (SEM) image of the metal Y doped YAG transparent ceramic prepared in Example 2.

[0048] Figure 4 are transmittances of the metal Y doped YAG transparent ceramic of Example 1, Example 2, Example 3, respectively. DETAILED DESCRIPTION

[0049] The application will be further described in conjunction with specific examples. It should be understood that these examples are only used to illustrate the application and not used to limit the scope of protection of the application. Furthermore, it should be understood that after reading the disclosure of the application, those skilled in the art can make various modifications or changes to the application, and these equivalent forms also fall within the scope of protection of the application.

[0050] Example 1

[0051] Y2O3, Al2O3, metal Y powder according to the chemical composition (Y x Y 1-x )3Al5O 12-3x are weighed and mixed (the first Y represents metal Y powder) to obtain a mixed oxide, wherein x = 0.0001; anhydrous ethanol is used as a sand milling solvent, the mass of the anhydrous ethanol is 90% of the mass of the mixed oxide, after sand milling, drying is performed at 55°C, and then the powder is passed through a 50-150 μm sieve.

[0052] The sieved powder is formed in a steel mold at an initial pressure of 20 MPa, then in an oxygen atmosphere, the temperature is raised from room temperature to 400°C at a rate of 180°C / h, then the temperature is raised from 400°C to 800°C at a rate of 120°C / h, after degassing at this temperature for 10 hours, natural cooling is performed, and then cold isostatic pressing is performed at 200 MPa, and after pressure holding for 120 s, further densification is performed to obtain a green body;

[0053] The green body is sintered at 1700°C under a vacuum degree higher than 10 -3 Pa, and the temperature is held for 10 hours. Then, annealing is performed, and after grinding and polishing, a metal Y doped YAG transparent ceramic is finally obtained.

[0054] Example 2

[0055] Y2O3, Al2O3, metal Y powder according to the chemical composition (Y x Y 1-x )3Al5O 12-3XThe weighed and mixed powders (the first Y represents metal Y powder) are obtained, wherein x = 0.001; the sand milling solvent is anhydrous ethanol, the mass of the anhydrous ethanol is 90% of the mass of the mixed oxides, and the sand milling is followed by drying at 55°C and then sieving through a 50-150 μm sieve.

[0056] The sieved powders are formed in a steel mold under an initial pressure of 20 MPa, and then, in an oxygen atmosphere, the temperature is raised from room temperature to 400°C at a temperature raising rate of 180°C / h, and then the temperature is raised from 400°C to 800°C at a temperature raising rate of 120°C / h, the powders are degassed at the temperature of 800°C for 10 hours, and then the green compact is obtained after natural cooling and further densification through cold isostatic pressing at 200 MPa for 120 seconds.

[0057] The green compact is sintered at 1700°C under a vacuum degree higher than 10 -3 Pa for 10 hours, and then, after annealing and polishing, the metal Y doped YAG transparent ceramic is finally obtained.

[0058] Example 3

[0059] Y2O3, Al2O3 and metal Y powder are weighed and mixed according to the chemical composition (Y x Y 1-x )3Al5O 12-3x , wherein x = 0.01; the sand milling solvent is anhydrous ethanol, the mass of the anhydrous ethanol is 90% of the mass of the mixed oxides, and the sand milling is followed by drying at 55°C and then sieving through a 50-150 μm sieve.

[0060] The sieved powders are formed in a steel mold under an initial pressure of 20 MPa, and then, in an oxygen atmosphere, the temperature is raised from room temperature to 400°C at a temperature raising rate of 180°C / h, and then the temperature is raised from 400°C to 800°C at a temperature raising rate of 120°C / h, the powders are degassed at the temperature of 800°C for 10 hours, and then the green compact is obtained after natural cooling and further densification through cold isostatic pressing at 200 MPa for 120 seconds.

[0061] The green compact is sintered at 1700°C under a vacuum degree higher than 10 -3 Pa for 10 hours, and then, after annealing and polishing, the metal Y doped YAG transparent ceramic is finally obtained.

[0062] Figure 1 The actual photos of the metal Y doped YAG transparent ceramics obtained in Example 1, Example 2 and Example 3 of the present application are shown in Figs. 1, 2 and 3 respectively. Figure 1As can be seen from the table, with the increase of the content of the metal element yttrium in the raw material specific gravity (x = 0.0001-0.01), the transparency of the prepared doped YAG transparent ceramic gradually changes from foggy to transparent and then appears to be dotted. Specifically, the doped YAG transparent ceramic prepared in Example 1 has a foggy transparency; the doped YAG transparent ceramic prepared in Example 2 has a transparent and non-dotted transparency; and the doped YAG transparent ceramic prepared in Example 3 has a transparent and partially dotted transparency.

[0063] Figure 2 The X-ray diffraction patterns of the doped YAG transparent ceramic prepared in Example 1, Example 2 and Example 3 of the present application are shown in the following table. Figure 2 As can be seen from the table, compared with the standard card (PDF #33-0040) of YAG, the phase of the sintered ceramic sample is YAG phase as a whole.

[0064] Figure 3 The SEM image of the doped YAG transparent ceramic prepared in Example 2 of the present application is shown in the following table. Figure 3 As can be seen from the table, the prepared YAG transparent ceramic has a small grain size (about 3-6 μm) and dense grains, and the grain boundary is obvious without obvious pores.

[0065] Figure 4 The transmittance spectrum of the doped YAG transparent ceramic prepared in Example 1, Example 2 and Example 3 of the present application is shown in the following table. The transmittance (2000 nm waveband) of the doped YAG transparent ceramic prepared in Example 1-3 is 72.7%, 85.0% and 83.7% respectively. This data is consistent with the data in the table. Figure 1 As can be seen from the table, the doped YAG transparent ceramic prepared in Example 2 has the highest transparency, the doped YAG transparent ceramic prepared in Example 3 has the second highest transparency, and the doped YAG transparent ceramic prepared in Example 1 has the lowest transparency. Figure 1

[0066] In addition, the thermal conductivity and mechanical properties of the doped YAG transparent ceramic prepared in Example 1-3 are further measured, and the test results are shown in Table 1.

[0067] Table 1

[0068] Thermal conductivity Vickers hardness Example 1 15.3 w / (m-k) 15 GPa Example 2 16.0 w / (m-k) 17 GPa Example 3 16.7 w / (m-k) 19 GPa

[0069] As can be seen from the data in Table 1, the doped YAG transparent ceramic of the present application has excellent thermal conductivity and mechanical properties, and can be widely used in the fields of medium and high energy physics, medical devices and the like, and is an ideal transparent armor material and laser gain medium material.

[0070] The above describes the embodiments of the present application. However, the present application is not limited to the above-described embodiments. Any modification, equivalent replacement, improvement and the like made within the spirit and principle of the present application shall be included in the protection scope of the present application.​

Claims

1. A metal Y-doped YAG transparent ceramic, characterized in that, The chemical formula of the ceramic is (Y x Y 1-x )3Al5O 12-3x ; wherein, 0 < x 0.01; the first Y represents metal Y and exists in a doped form; the second Y comes from yttrium in yttria, as a main matrix, and exists in a crystal lattice.

2. The YAG transparent ceramic doped with metal Y according to claim 1, characterized in that, x=0.0001~0.01。 3. The method for preparing the metal Y-doped YAG transparent ceramic according to claim 1 or 2, characterized in that, The preparation method comprises the following steps: 1) according to the chemical formula (Y x Y 1-x )3Al5O 12-3x , a certain mass of (i) Y2O3, (ii) Al2O3, (iii) metal Y is mixed to obtain a raw material mixture, and further added with ethanol to obtain a mixture; 2) sand grinding the mixture in step 1), and drying; 3) primary pressing, glue discharging, and cold isostatic pressing; 4) vacuum sintering to obtain the metal Y-doped YAG transparent ceramic.

4. The preparation method according to claim 3, characterized in that, In step 1), the ethanol is anhydrous ethanol; the mass of the ethanol is 80-120% of the mass of the raw material mixture.

5. The production method according to claim 3 or 4, characterized by, In step 2), the drying temperature is 40-90℃; The drying time is 10h-48h.

6. The production method according to claim 3 or 4, characterized by, In step 2), the mixture after drying is further ground, then sieved, and then step 3) is performed. In the sieving step, a 50μm-150μm sieve is used.

7. The production method according to claim 3 or 4, characterized by, In step 3), the pressure of the primary pressing is 5-20MPa; The primary pressing time is 10s-60s; The glue discharging is performed in an oxygen atmosphere; The glue discharging temperature is 100-1000℃; The temperature rising process of the glue discharging process is performed in two stages.

8. The production method according to claim 3 or 4, characterized by, In step 4), the vacuum sintering temperature is 1650-1950℃; The vacuum degree in the vacuum sintering is at least 10 -2 Pa; The holding time is 5h-30h.

9. Use of the yttrium-doped YAG transparent ceramic according to any one of claims 1 to 2, characterized in that, The material is used in the field of medium-high energy physics or medical equipment.

10. A transparent armor material or laser gain medium material, characterized in that, The material comprises the metal Y-doped YAG transparent ceramic according to any one of claims 1-2.

Citation Information

Patent Citations

  • Yttrium aluminum garnet powder without sintering aid, yttrium aluminum garnet ceramic, and preparation method and application thereof

    CN111925202A

  • Method of producing transparent ceramic of yttrium aluminium garnet

    RU2584187C1